INTERIOR HUNIAN DENGAN GAYA HIDUPNEW MINIMALISM: Sebagai Strategi Hidup Berkelanjutan - Utami, Ni Kadek Yuni (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
The rise of a new minimalism lifestyle, by giving priority to function, quality, durability, decluttering and reducing extranous items and living with something essential only, adopted in interior that can applied in layout, furniture design, material that support minimalism lifestyle. The purpose of this paper is to analyze the interior design of residential with new minimalism lifestyle that can be applied as one of sustainable living strategies with adescriptive approach to get how a new minimalismapplied to a house, limited to bedrooms, wardrobe, kitchen.